Experimental exposure of blue mussel beds to soft and rigid macroplastics in the winter reveals litter entrapment but no physiological effects - Kumpitsch, Luisa; Schindel, Annika; Lenz, Mark (Frontiers in Marine Science, 2025)
Macroplastic items like bags, bottles, and containers dominate marine litter, yet their effects on habitats and ecosystems remain understudied. Blue mussels (Mytilus edulis, Mytilus trossulus) form beds that support biodiversity and provide important ecosystem services. The goal of this work was to investigate in an experiment how planar plastic debris, rigid or soft, influences mussel aggregates with regard to their structure and their physiological performance. Mussel individuals were collected in the Kerteminde Fjord and were transferred to a laboratory where they were allowed to form small aggregates on PVC plates (30 individuals each). During formation, half of the aggregates were polluted with planar plastic litter of a defined type (soft PE bags or rigid fragments of PET bottles) and amount, while the other half remained without incorporated macroplastics. All aggregates were then deployed in the fjord for 14 weeks in the winter 2020/21. Afterwards, we measured the cumulative filtration and respiration rates, filtration-to-respiration ratios, condition indices, growth rates, aggregate rugosities, and byssus strengths. Rigid plastics significantly enhanced aggregate rugosity, while all physiological responses as well as byssus formation remained unchanged. The latter might, at least partly, have been due to the fact that we conducted the experiment in winter, when mussel metabolism is substantially reduced. Notably, soft plastics were often concealed within aggregates, and this was presumably caused by the movements of the mussels. This finding suggests that mussel beds may act as sinks for plastic litter, while soft and film-like litter items can be fully embedded in their three-dimensional matrix.